2011
DOI: 10.3389/fnint.2011.00060
|View full text |Cite
|
Sign up to set email alerts
|

Slow Modulation of Ongoing Discharge in the Auditory Cortex during an Interval-Discrimination Task

Abstract: In this study, we recorded single unit activity from rat auditory cortex while the animals performed an interval-discrimination task. The animals had to decide whether two auditory stimuli were separated by either 150 or 300 ms, and go to the left or right nose poke accordingly. Spontaneous firing in between auditory responses was compared in the attentive versus non-attentive brain states. We describe the firing rate modulation detected during intervals while there was no auditory stimulation. Nearly 18% of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…To obtain single unit activity, waveforms were clustered automatically using the valley-seeking algorithm in Plexon Offline Sorter (Koontz and Fukunaga, 1972; Abolafia et al, 2011). After clustering, waveforms were visually inspected in order to remove clusters containing noise or artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain single unit activity, waveforms were clustered automatically using the valley-seeking algorithm in Plexon Offline Sorter (Koontz and Fukunaga, 1972; Abolafia et al, 2011). After clustering, waveforms were visually inspected in order to remove clusters containing noise or artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…The role of sensory areas—especially primary sensory areas—has long been regarded as providing a faithful representation of the external world (Felleman and Van Essen, 1991; Goldman-Rakic, 1988; Kandel et al, 2000; Miller and Cohen, 2001); several studies have shown that these areas convey sensory information (Ghazanfar and Schroeder, 2006; Hubel and Wiesel, 1962, 1968; Lemus et al, 2010; Liang et al, 2013), while others have shown causal roles in sensory perception (Glickfeld et al, 2013; Jaramillo and Zador, 2011; Sachidhanandam et al, 2013; Znamenskiy and Zador, 2013). However, this view has recently been challenged by observations that sensory cortices represent not only stimulus features but also non-sensory information (Abolafia et al, 2011; Ayaz et al, 2013; Brosch et al, 2011; Fontanini and Katz, 2008; Gavornik and Bear, 2014; Jaramillo and Zador, 2011; Keller et al, 2012; Niell and Stryker, 2010; Niwa et al, 2012; Pantoja et al, 2007; Samuelsen et al, 2012; Serences, 2008; Shuler and Bear, 2006; Stanisor et al, 2013; Zelano et al, 2011). In the visual modality, it has been shown that V1 can predict the learned typical interval between a stimulus and a reward (Chubykin et al, 2013; Shuler and Bear, 2006) and that the ability to learn such intervals depends on cholinergic input from the basal forebrain (Chubykin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Slow firing changes can start after auditory stimuli, reinforcers and behavioral responses, end with reinforcers and possibly with auditory stimuli and behavioral responses, and depend on the expected reward (Komura et al, 2001;Brosch et al, 2011b). A few other studies have also described slow firing changes in auditory cortex for different tasks (Kitzes et al, 1978;Gottlieb et al, 1989;Shinba et al, 1995;Quirk et al, 1997;Armony et al, 1998;Abolafia et al, 2011). Slow firing changes have been proposed to be related to anticipating, memorising and associating task elements (Brosch et al, 2011a,b).…”
Section: Introductionmentioning
confidence: 99%